Physical and mechanical behaviour of polysiloxane filled silica sheet - Mohamad Yahya, Sufiah (2017)
Polysiloxane (POS) is a unique polymer and contains silicone and oxygen in polymer chains. Degradation is a common problem of polymer material which leads to material properties decreased. Heat, light and chemicals are the main cause of polymer degradation (Moeller, 2008). In order to reduce the tendency of polymer to degradation, the role of silica as filler will be studied. Silica offers high thermal properties, and thus by combining polysiloxane and silica, it is expected that the polysiloxane filled silica composites thermal properties will be enhanced. Since silica acts as a reinforcing filler in polysiloxane matrix, it is expected to improve the mechanical properties (tensile and energy absorbed) of the composites. The study embarks on to determine of different curing temperature (room temperature, 65°C and 100°C) as critical variable in casting of POS-SiO2 composite also to investigate the effect of weight percentage (wt%) of SiO2. Parameter for wt% of SiO2 is 0wt¾ to 12wt%. The characteristics of POS reinforced SiO2 were analysed in terms of microstructure Field emission scanning electron microscope (FESEM), phase analyses X-ray Diffraction (XRD), thermal properties analyses thermogravimetry analysis (TGA), molecular analysis using fourier transformation infrared spectroscopy (FTIR). Distribution of SiO2 in POS- SiO2 composite are agglomeration through FESEM analysis for all compositions. Strength analysis and Young Modulus were performed using Universal Tensile Machine (UTM). The factors of different curing temperature and wt% ofSiO2added as filler are improved the value of strength and Young Modulus POS- SiO2 composites. Energy absorption is using the high speed puncture machine. The value of the energy absorption increase with increasing of curing temperature during casting composites. The conclusion is factors of wt% of SiO2 as a filler and different curing temperature are important and gave effect to POS- SiO2 composites.